Mitigasi Banjir Untuk Tercapainya Sanitasi Lingkungan - Assiddiqi Ridwan, Hamdi; Sumpena, Deden; Herdiana, Dedi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2024)
The aim of this research is to determine 1) The flood mitigation program carried out by the Cibiru Hilir village government 2) The implementation of the flood mitigation program 3) The results obtained from the Cibiru Hilir village government's flood mitigation program to achieve environmental sanitation. The research method uses qualitative methods. The theory used is Tangkilisian's theory of public policy (2003; 2). The results of the research show that the Cibiru Hilir village government has several public policies in three mitigation programs, namely, building water retention areas, purchasing heavy equipment in the form of water pumps, and outreach to the community regarding flood management. In its implementation, the Cibiru Hilir village government went through the stages of planning, implementation, and also finding inhibiting factors. The results obtained show that the Cibiru Hilir village government in dealing with existing flood problems has had a positive impact on the community and also on the flood problems in Cibiru Hilir village to achieve good environmental sanitation and a community that is empowered against flood disasters.